Performance of Oropharyngeal Swab Testing Compared With Nasopharyngeal Swab Testing for Diagnosis of Coronavirus Disease 2019—United States, January 2020–February 2020. (16th June 2020) - Patel, Monita R; Carroll, Darin; Ussery, Emily; Whitham, Hilary; Elkins, Christopher A; Noble-Wang, Judith; Rasheed, James Kamile; Lu, Xiaoyan; Lindstrom, Stephen; Bowen, Virginia; Waller, Jessica; Armstrong, Gregory; et al.
Abstract: Among 146 nasopharyngeal (NP) and oropharyngeal (OP) swab pairs collected ≤7 days after illness onset, Real-Time Reverse Transcriptase Polymerase Chain Reaction assay for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 RT-PCR) diagnostic results were 95.2% concordant. However, NP swab cycle threshold values were lower (indicating more virus) in 66.7% of concordant-positive pairs, suggesting NP swabs may more accurately detect the amount of SARS-CoV-2.